Stage fright - Cabot, Meg (New York Scholastic Press, 2009)
Allie's theatrical hopes are crushed when, instead of being cast as the princess, she is given the role of the evil queen in the fourth-grade class play
Hurg
5 8
Keywords: Behavior -- Fiction; Family life -- Fiction; Friendship -- Fiction